Implementasi PBL dan PjBL dengan Model Lesson Study di SMA/K Se-Kota Kasongan: Implementation of PBL and PjBL with the Lesson Study Model in SMA/K throughout Kasongan City - Artuti, Emy; Mairing, Jackson Pasini; Ratnawati, Oktaviana Ainun; Pancarita, Pancarita; Aritonang, Henry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
A lesson study is a plan of models, strategies, approaches, methods, and techniques effectively implemented in the classroom. The objectives of community service activities are as follows: Assist mathematics teachers in creating learning tools through lesson plans, LKPD, learning videos, PBL, and PjBL-based assessments, as well as increase teachers' understanding in compiling and planning to learn so that it is more effective and has an impact on student's abilities. Service activities are carried out in 2 stages of lesson study, including Stage 1 Plan, held on Tuesday, August 2023, at SMAN 2 Kasongan. Stages 2 and 3 were implemented on Thursday, September 2023, by teacher readiness and implementation location at SMKN 1 Katingan Hilir. After implementation, all teachers provide reflections and share experiences to improve the learning that has been implemented. The PkM results have been uploaded on the YouTube channel of the UPR Mathematics Education Study Program.